2014
DOI: 10.1039/c3nr05820d
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-free and strongly adhesive silver nanowire networks with long-term reliability by introduction of a nonconductive and biocompatible polymer binder

Abstract: As a promising candidate to replace the brittle and expensive transparent indium tin oxide (ITO) conductor, the use of silver nanowire (AgNW) networks still involves issues such as high-temperature post-treatments and poor substrate adhesion for industrial application. Here a room-temperature soldering and one-step solution method is developed to achieve high-performance Ag nanowire transparent conductive films (TCFs). A nonconductive binder is prepared from poly(dopamine) and alginic acid which contains abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 31 publications
1
85
2
Order By: Relevance
“…The high and broad transmission spectrum with excellent low R sheet in this sample corresponds to a very high FoM of 385.8.23 This value is among the highest reported values in TCEs,16,[47][48][49] indicating that s-MoO x -treated AgNWs provide a promising alternative for ITO,70 The total transmittance of the TCE decreases with an increase in the 40 concentration of the s-MoO x precursor solution and the thickness of the e-MoO x layer.…”
mentioning
confidence: 49%
“…The high and broad transmission spectrum with excellent low R sheet in this sample corresponds to a very high FoM of 385.8.23 This value is among the highest reported values in TCEs,16,[47][48][49] indicating that s-MoO x -treated AgNWs provide a promising alternative for ITO,70 The total transmittance of the TCE decreases with an increase in the 40 concentration of the s-MoO x precursor solution and the thickness of the e-MoO x layer.…”
mentioning
confidence: 49%
“…Actually, it is also reported that solvent evaporation and polymer shrinkage during the coating and heating process could even improve the wire-wire contact. 25,37,45 In the present work, the nanowires were well washed before coating and the thick PVP layer adsorbed on the nanowire surface has been drastically removed, thus the nanowire contact has been already improved in this step. Furthermore, the long nanowires used in this study with average length over 40 µm are not so sensitive to the wire-wire contact resistance change as the relatively short ones (average length of 10~20 µm).…”
Section: Resultsmentioning
confidence: 99%
“…polyethylene terephthalate (PET) or polyethylene napthalate (PEN)), they exhibit high optical transmittance in the visible part of the spectrum combined with low sheet resistance. [ 19,20 ] Moreover, for an application under outdoor conditions, seve ral aspects have to be considered. The layer stack should be intrinsically stable to ensure a long lifetime.…”
Section: Doi: 101002/aenm201502432mentioning
confidence: 99%